Street View Pada Aplikasi Informasi Pusat Makanan Khas Kabupaten Wonosobo - Hendriyanto, Hendriyanto; Wismarini, TH. Dwiati (Information Technology and Telematics, 2018)
Abstract - Wonosobo Regency is one area that has a variety of typical food for visitors. In Wonosobo District there are a lot of souvenirs for old or new foods in large numbers, but there is rarely information about the center of souvenirs for the public. The purpose of this learning is to create an application for information about the typical food souvenir center in Wonosobo District which has a street view feature. This system is designed using Google Maps API as a map server, notepad ++ and MySQL as the database. The result of this research is street view in the application of information center for souvenirs typical of Wonosobo Regency based on Webgis, which allows information supported by the street view feature to provide the right information to be accessed by various parties.